Infusion of Megakaryocytic Progenitor Products Generated from Cord Blood Hematopoietic Stem/Progenitor Cells: Results of the Phase 1 Study - Xi, Jiafei (Public Library of Science, 2013)
BACKGROUND: Currently, a constant shortage in the supply of platelets has become an important medical and society challenge, especially in developing country, and the in vitro production of megakaryocytic progenitor cells (MPs) from cord blood could represent an effective platelet substitute. In the present study, our objective was to determine the safety and feasibility of ex vivo generated MPs in patients. METHODS AND FINDINGS: MPs were produced and characterized from cord blood mononuclear cells under a serum free medium with cytokines. We investigated the feasibility of expansion and infusion of cord blood-derived MPs in 24 patients with advanced hematological malignancyes. The primary end point was the safety and tolerability of the infusion of cord blood-derived MPs. No adverse effects were observed in patients who received ex vivo-generated cells at concentrations of up to a median value of 5.45×10(6)cells/kg of body weight. With one year follow-up, acute and chronic GVHD had not been observed among patients who received MPs infusion, even without ABO blood group and HLA typing matching. CONCLUSIONS: These initial results in patients are very encouraging. They suggest that infusion of cord blood-derived MPs appears safe and feasible for treatment of thrombocytopenia. TRIAL REGISTRATION: www.chictr.org ChiCTR-TCH-09000333.